Changes in alpha-7 nicotinic acetylcholine receptor and macrophage polarization state participate in the regulation of cervical remodeling in pregnant rats. Issue 5 (25th July 2019) - Yang, Jinying; Lai, Yumian; Chen, Juanhua; Lin, Baohua; Zhou, Bei; Han, Xinjia
Abstract: To test the hypothesis that changes in alpha-7 nicotinic acetylcholine receptor (α7nAChR) expression on macrophages and macrophage polarization participate in cervical remodeling during normal pregnancy, pregnant rats from gestational days (GDs) 14, 16, 18, 20, and 22 were used in the present study. The expression of α7nAChR on macrophages and the numbers of M1 and M2 macrophages were detected by double immunofluorescence staining. The levels of α7nAChR and collagens were detected by western blotting. M1 markers (inducible nitric oxide synthase and inflammatory cytokines) and M2 markers (arginase 1, anti-inflammatory cytokines) were detected to evaluate the macrophage polarization state by immunohistochemistry staining, western blotting, and the enzyme-linked immunosorbent assay. Matrix metalloproteinase 9 (MMP-9) expression was determined by immunohistochemistry staining and western blotting. We found that the α7nAChR expression on macrophages significantly decreased on GD22 compared to GDs 14, 16, 18, and 20. There was an increased number of M1 macrophages and decreased number of M2 macrophages in late pregnancy. The expression of M1 macrophage biomarkers was much higher on GDs 20 and 22 than on GDs 14, 16, and 18, but expression of M2 biomarkers decreased on GDs 20 and 22 compared to GDs 14, 16, and 18. MMP-9 expression was higher on GD22 than on GDs 14, 16, 18, and 20, and collagen expression significantly decreased on GDs 18, 20, and 22 compared to GD14. Our results indicated that the decreased expression of α7nAChR and increased number of M1 macrophages are associated with cervical remodeling. Abstract : Summary sentence : The decrease in α7nAChR expression contributes to cervical ripening in late pregnant rats without infection, possibly by inducing M1 macrophage polarization and inflammatory responses.